ABILITY OF THE BLEND POLICY IN CONTROLLING THE BALANCE OF TRADE BALANCE DUE TO FIVE COVID-19 TOP ASIAN EXPORT COUNTRIES (FITASPORTRIES) - Zuhro, Nabila Az; Efendi, Bakhtiar; Nasution, Lia Nazliana; Sari, Wahyu Indah (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2020)
The COVID-19 outbreak has not only had a major impact on the world's health, but also has an impact on people's lifestyles, which are becoming increasingly consumptive. This is in line with the implementation of policies carried out in various countries that have caused changes in the level of trade balance between countries, especially in the 5 countries that are the largest exporters in Asia. Therefore, this study aims to analyze the contribution of the interaction of monetary policy variables with fiscal policy in controlling the balance of trade balance in the current economic conditions that are being hit by the COVID-19 pandemic. This type of research is a quantitative analysis using secondary data with a time series from November 2019 to February 2021 (time series). The analytical method used is Vector Autoregression (VAR), seen from the analysis of Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD), Panel AR Distributed Lag Models (ARDL) and Paired Sample Test. The results of the IRF analysis show that the stability of the response of all variables is formed in the 8th period or the medium and long term, where the response of other variables to changes in one variable shows different variations from positive to negative responses or vice versa vice versa, and there are variables whose responses remain positive or negative. remain negative from short to long term. The results of the FEVD analysis show that the dominant variables in the short, medium and long term are Trade Balance, SB, JUB and INF, while the dominant variables over other variables are SB and EXCHANGE. Then the results of the ARDL Panel as a whole in the long term turned out that TAX, GOV and GDP had an effect on the balance of trade in the Five Top Asian Export Countries. The results of the Difference Test analysis showed that Japan and Indonesia experienced a trade balance surplus. The results also showed that there were significant differences both before and during the COVID-19 pandemic.